2017
DOI: 10.1186/s12958-017-0254-5
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular injection of RFRP-3 delays puberty onset and stimulates growth hormone secretion in female rats

Abstract: BackgroundPuberty onset is a complex, organized biological process with multilevel regulation, and its physiopathological mechanisms are yet to be elucidated. RFRP-3, the mammalian ortholog to gonadotropin-inhibitory hormone, is implicated in inhibiting the synthesis and release of gonadotropin in mammals. However, it is unclear whether RFRP-3 participates in regulating pubertal development.MethodsThis study investigated the functional significance and regulatory mechanism of hypothalamic RFRP-3 neuropeptide i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…Delayed puberty in our study, may be due to increased Rfrp expression. Similarly, in a study by Han et al (26) it was shown that intracerebroventricular injection of RFRP-3 between days 28 and 36, at the time of puberty onset, delayed vaginal opening in rats. Furthermore, Rfrp expression in DMN decreased during early pre-pubertal stages in the mouse.…”
Section: Discussionmentioning
confidence: 69%
“…Delayed puberty in our study, may be due to increased Rfrp expression. Similarly, in a study by Han et al (26) it was shown that intracerebroventricular injection of RFRP-3 between days 28 and 36, at the time of puberty onset, delayed vaginal opening in rats. Furthermore, Rfrp expression in DMN decreased during early pre-pubertal stages in the mouse.…”
Section: Discussionmentioning
confidence: 69%
“…On the other hand, GPR147 mRNA expression in female rats increases from P16, peaks at P28, and decreases from P35 . Central administration of GnIH (RFRP3) from P28 to P36 twice a day significantly decreases serum LH and estradiol concentration, delay uterine maturation and vaginal opening in female rats . These results suggest that decreases in GnIH and/or GPR147 may also facilitate puberty in male and female rats.…”
Section: Regulation Of Pubertymentioning
confidence: 89%
“…To evaluate the hypothalamic expressions of Lin28a and Lin28b mRNA and let7a and let7b miRNA, hypothalamic samples were collected and stored at −80°C. The uteruses and ovaries were immediately dissected out of the surrounding fat by opening the abdominal cavity and were weighed to evaluate the organ coefficients according to the organ index formula ([organ wet weight (g)/body weight (g)] × 10 −4 ) [ 49 ].…”
Section: Methodsmentioning
confidence: 99%